Peningkatan Pengetahuan dan Keterampilan Ibu Rumah Tangga Nelayan dalam Diversifikasi Pengolahan Kerang Kalandue - Ramli Ramli; Abdul Wafi; Siti Nur Aisyah Jamil; Ismi Jasila; Lovi Sandra (Jurnal Pengabdian Masyarakat (abdira), 2022)
The increased knowledge and skills of fishermen housewives in diversification the processing of kalandue shellfish is expected to increase the added value of kalandue shellfish which in turn will improve the economic level of fishermen housewives. The stages of this service activity include: survey and planning; implementation preparation; implementation; and Program sustainability strategy. This community service activity has a positive impact on the group of fishermen housewives, namely increasing knowledge and skills in diversification the processing of kalandue shellfish, business management, marketing and promotion strategies as well as maintaining environmental sustainability and the balance of marine ecosystems. Program sustainability strategies, namely establishing an organizational structure for business groups of fishermen housewives, collaborating with the government and building partnerships.